The Influence of Love of Money and Machiavellianism on Accounting Students' Ethical Perceptions: Empirical Study on Accounting Students at Bandar Lampung University - Nadelia Nisa Karima; Luke Suciyati Amna (Cita konsultindo, 2024)
This research aims to find out and analyze influence Love Of Money and Machiavellian On the Ethical Perceptions of Accounting Students at Bandar Lampung University. Population is the sum of all possible values, calculated and measured, so population from this research are Accounting Students from Bandar Lampung University. The samples in this study were identified using the lemshow formula sample size is found amounting to 100 respondents. This analysis uses statistical calculations to facilitate testing for data analysis, therefore the above analysis uses tools SPSS 25 application. This research uses multiple linear regression analysis or tests, coefficient of determination tests and t tests. The results of this research state that Love Of Money and Machiavellian influence partially and anova on the Ethical Perceptions of Accounting Students at Bandar Lampung University.